Os desafios da escola na constituição da espiritualidade de estudantes do Ensino Médio de escolas da cidade de São Paulo - Ferreira, Patrick Vieira (2021)
This dissertation’s goal was to investigate the implications of the role of contemporary schools for the constitution of the spirituality of high school students in the city of Sao Paulo, from the point of view of such students. The theoretical foundation is based on national and international researchers. Three instruments for producing and collecting data were used: 1) a systematic review that sought to identify different conceptions of spirituality in current studies that resorted to works published in two academic databases: CAPES Theses and Dissertations Catalog and the Scientific Electronic Library Online - SciELO, in the period from 2004 to 2018. The organization of the different studies allowed for the emergence of five categories, which were later used to analyze the documents, the Political-Pedagogical Projects, and the data obtained in the discussion groups; 2) an analysis of official documents and Political-Pedagogical Projects belonging to the schools under study, in order to gather and identify different conceptions of spirituality in them; 3) the application of a survey consisting of 26 closed questions and two open questions, to high school students from four schools, two of which were confessional schools and two public schools, and 4) discussion groups - conducted in two schools -, one of which was a confessional school and another one, a public school, seeking to portray the role of the school in the constitution of spirituality, according to the opinion of the young people who participated in the survey. For the analysis of the data collected from the responses to the survey we used the statistical program known as the Statistical Package of Social Sciences (SPSS), using the so-called Student's t test for descriptive analysis of frequencies, variation and inferential statistics of some questions. For documentary analysis, we resorted to categorization. Finally, our understanding of the discourse of the discussion groups was inspired by Prose Analysis. When we analyzed the documents, we observed the existence of a multifaceted vision of spirituality. A more integrative approach to national educational guidelines is needed; however, we observed the absence of references to the spiritual dimension in state guidelines. The analysis also showed that the conception of spirituality by young people and adolescents fits into the following categories: 1) Spirituality as a protective factor; 2) Spirituality as part of the integral being; 3) Spirituality as the meaning of life; and 4) Spirituality linked to religiosity. We found different emphases, in confessional and public schools, regarding the meanings of spirituality. From the analysis, we understand that the role of the school in the constitution of spirituality is to: 1) provide environments in which the spiritual dimension can be explored; 2) offer psycho-emotional help to students; 3) allow teachers to be mediators for deeper knowledge and 4) help teachers develop a relationship with students based on humanizing practices